Astrocyte Function Is Affected by Aging and Not Alzheimer’s Disease: A Preliminary Investigation in Hippocampi of 3xTg-AD Mice - Bronzuoli, Maria Rosanna; Facchinetti, Roberta; Valenza, Marta; Cassano, Tommaso; Steardo, Luca; Scuderi, Caterina (Frontiers in Pharmacology, 2019)
Old age is a risk factor for Alzheimer’s disease (AD), which is characterized by hippocampal impairment together with substantial changes in glial cell functions. Are these alterations due to the disease progression or are they a consequence of aging? To start addressing this issue, we studied the expression of specific astrocytic and microglial structural and functional proteins in a validated transgenic model of AD (3×Tg-AD). These mice develop both amyloid plaques and neurofibrillary tangles, and initial signs of the AD-like pathology have been documented as early as three months of age. We compared male 3×Tg-AD mice at 6 and 12 months of age to their wild-type age-matched counterparts. We also investigated neurons by examining the expression of both the microtubule-associated protein 2 (MAP2), a neuronal structural protein, and the brain-derived neurotrophic factor (BDNF). The latter is indeed a crucial indicator for synaptic plasticity and neurogenesis/neurodegeneration. Our results show that astrocytes are more susceptible to aging than microglia, regardless of mouse genotype. Moreover, we discovered significant age-dependent alterations in the expression of proteins responsible for astrocyte-astrocyte and astrocyte-neuron communication, as well as a significant age-dependent decline in BDNF expression. Our data promote further research on the unexplored role of astroglia in both physiological and pathological aging.